Impact of chitosan-beeswax edible coatings on the quality of fresh strawberries (Fragaria ananassa cv Camarosa) under commercial storage conditions - Velickova, Elena (2016)
Chitosan-based edible coatings were used to prolong the shelf-life of strawberries stored at 20 C and 35 e40% RH. Strawberries were coated with four different coating formulations (chitosan as monolayer, three layer coating consisting of separate beeswaxechitosanebeeswax layers, three layer coating where chitosan was crosslinked with sodium tripolyphosphate, TPP, and composite). The effectiveness of the coatings was evaluated by the changes of several parameters: fungal infection, weight loss, respiration rate, skin and flesh color, firmness, pH value, titratabale acidity, soluble solids content, reducing sugars content and sensory evaluation. The coatings, especially the three-layer coatings, significantly decreased the senescence and weight loss of the fruits. They modified the respiration rates of the strawberries and slowed down their metabolism as shown by the retention of the color and the texture of the tissue. Sensory evaluation of the coated strawberries showed that the chitosan and composite coatings gave better visual appearance and taste and were therefore more preferable by 90% of the judges than the three-layer coatings, even though the later had higher protective effect of the overall quality of the strawberries